Fragility Fracture of Proximal Tibia in A Wheelchair-Bound 54-Year-Old Female Patient - Davidia, Zaky; Abirama, Atria (SAFE-Network, 2024)
Sedentary behavior is one of the risk factors of fracture, in which mild activity was found to be inversely associated with hip, vertebral, and total fracture. Other study also found non-linear association of fracture risk with lower and higher physical activity was associated with higher risk of any fracture compared to a mean physical activity. In this study, we reported a 54-year-old wheelchair bound female with fracture on the proximal tibia cause by low-energy trauma. This research underscores the importance of early identification of fracture risk factors, especially in vulnerable populations such as older adults who are wheelchair-bound. Early interventions that include lifestyle changes, increased physical activity, and nutritional management are essential to prevent further fractures and improve bone health. Identifying the risk of fractures on elderly patient may be beneficial for prevention of fractures especially in wheelchair-bound elderly individual.